Phytochemical Evaluation of Lepidium meyenii, Trigonella foenum-graecum, Spirulina platensis, and Tribulus arabica, and Their Potential Effect on Monosodium Glutamate Induced Male Reproductive Dysfunction in Adult Wistar Rats - Naglaa Gamil Shehab; Temidayo S. Omolaoye; Stefan S. Du Plessis; Surendra Singh Rawat; Nerissa Naidoo; Kholoud Y. Abushawish; Ayat Ahmed; Baraa Alaa; Heba Ihsan; Manar Abdelhalim; Mariam Ayman; Eslam El Nebrisi (MDPI AG, 2024)
Monosodium glutamate (MSG), a sodium salt derived from glutamic acid, is widely used in commercial food products to improve taste, quality, and preservation. However, its consumption may have detrimental effects on male reproductive function. Nevertheless, plant extracts, such as Lepidium meyenii (Maca), Trigonella foenum-graecum (Fenugreek), Spirulina platensis (Spirulina), and Tribulus arabica (Tribulus), may ameliorate these adverse effects. To this effect, the phytochemical properties of Lepidium meyenii, Trigonella foenum-graecum, Spirulina platensis, and Tribulus arabica were assessed, and their potential impact on MSG-induced impairment of reproductive parameters was examined. The phytochemical composition (steroids, terpenes, phenols, flavonoids) of the plants was profiled through spectrophotometry and the antioxidant activity was assessed using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. Thirty-six male Wistar rats were divided into six groups at random: a control group receiving distilled water, and five experimental groups (MSG, Maca, Fenugreek, Spirulina, and Tribulus) receiving 900 mg/kg/day of MSG dissolved in water for 45 days. Subsequently, the animals in the experimental groups were administered 500 mg/kg/day of the respective plant extract via oral gavage for an additional 35 days, while the MSG group continued to receive water only. Following the treatment period, the animals were sacrificed, and their reproductive tract organs were collected, weighed, and subjected to further analysis. Phytochemical analysis revealed the presence of diverse bioactive elements in the plant extracts, including phenolic and flavonoid compounds. Exposure to MSG negatively impacted total and progressive sperm motility, which was ameliorated by Lepidium meyenii treatment. Sperm morphology showed no significant differences among groups. Treatment of the phytochemical agents diminished histomorphometric alternations of the testicular length, germinal epithelium height, and number of cells in seminiferous tubules, which were caused by the initial administration of MSG. Testosterone and LH levels were reduced in the MSG group but improved in extract-treated groups. The study suggests Lepidium meyenii as a potential remedy for reproductive dysfunction. However, further investigation into its mechanisms and human safety and efficacy is warranted.